Ketoconazole in the treatment of cryptococcosis of the central nervous system - P. C. Trevisol-Bittencourt; J. W. A. S. Sander; C. S. Silvado; E. O. Wittig (Arquivos de Neuro-Psiquiatria)
Two patients with cryptococcosis of the CNS were treated with ketoconazole (KTZ), an imidazole derivative with fungistatic properties; they had either failed standard therapy (Amphotericin-B + 5-Flurocytosine) or suffred intolerable side-effects to it. Both patients were administered KTZ 800 mg/day as monotherapy for six months without interruption and both responded. One month after KTZ therapy was withdrawn, however, a relapse of the infection was seen in one case. Side-effects were minimal during the trial of treatment. KTZ could be a useful drug in some cases of neurocryptococcosis.